Pola Pengasuhan Orangtua dalam Membentuk Kemandirian Anak Usia 4-6 Tahun di Jorong Katimahar Kabupaten Pasaman Barat - Ria Desiska; Elise Muryanti (SELING: Jurnal Program Studi PGRA, 2020)
This study aims to see the parenting pattern in shaping children’s independence of aged 4-6 years in Jorong Katimahar West Pasaman Regency. This study used a mixed method, which combines quantitative and qualitative approaches that involve data collection techniques in the form of a questionnaires used is analysed by SPSS version 16. And by provided interviews and documentation. Based on the results of data processing using aquestionnaire shwert that most parents in Jorong Katimahar West Pasaman Regency district used democratic parenting as about as 60,95% the highest children’s independence of aged 4-6 years the parents answered often as about as 38.11%. And through interviews 5 respondents it can be concluded that parents used a pattern of democratic nurture and independence which is is quite good this results of this study it can be concluded that parenting patterns can shape the independence children.